New Appearances of the Leksema FRONT in the Language of Modern Ukrainian Mass Media - Navalna, Maryna; Shynkaruk, Vasyl; Kostusiak, Nataliia; Skliarenko, Olesia; Kushch, Nataliia; Buhaiova, Oksana (My University, 2023)
The article characterizes the lexeme front from the texts of modern Ukrainian means of mass communication, reveals new variants of figurative meanings of the lexical unit, traces the expansion of the scope of operation of lexemes on military topics in media materials of socio-political, medical, educational, cultural, and other topics; the functional and stylistic role of the lexeme front in the language of mass media is determined. In the investigation, for the study of the lexeme front in the language of Ukrainian mass media of the 21st century. method of observation and descriptive method are used as the main ones. At various stages of research, the method of functional analysis was used to determine the stylistic load of certain lexical units. It was concluded that due to a number of non-linguistic factors of socio-political direction, the modern Ukrainian language has been replenished with new variants and meanings of words. According to our observations, the lexeme front functions in different topics in the language of mass media of different forms of ownership. The analyzed lexeme is often used figuratively, which conveys generally the unity of Ukrainians in all types of professional activity during the period of full-scale war. The most widely represented adjectives are humanitarian, medical, economic, culinary, medical, which testifies to the actualization and importance of the corresponding spheres of activity during the war. In general, the expansion of the use of the lexeme front in combination with attributive linguistic units testifies to the broadest and largest unification of people of various professions, industries and spheres of activity in the struggle for a common goal - to defeat the enemy.
Keywords: lexeme front; non-linguistic factors; stylistic role; scope of use; figurative meaning; variants of meanings